Causal attributions following a cardiac event: Short- and long-term differences in health appraisals and outcomes. Issue 1 (3rd March 2016) - Bennett, Kymberley K; Clark, Jillian MR; Harry, Kadie; Howarter, Alisha D
This study examined attributions generated by cardiac rehabilitation patients shortly after experiencing a cardiovascular event, exploring whether attribution type was associated with health appraisals and outcomes concurrently and 21 months later. Attributions fell into three categories: controllable behavioral ones, uncontrollable biological ones, and stress-related causes. Linking attribution type to appraisals and outcomes showed that creating a behavioral attribution was beneficial in the short-term for control appraisals, but was associated with increased anxiety symptoms 21 months later. Thus, cardiac rehabilitation providers should encourage patients to maintain a future-focus that promotes perceived control over health promotion behaviors that reduce risk for recurrence.